J.W. Spencer (1851-1921): his Life in Canada, and his Work on Preglacial River Valleys - Middleton, Gerard V. (Geoscience Canada, 2004)
J.W. Spencer, born and buried in Dundas, Ontario, was a pioneer Canadian geomorphologist. After attending school in Dundas, he moved to Hamilton where he worked in a pharmacy, and was encouraged by local amateur geologists. He attended McGill University from 1871 to 1874, studied under William Dawson and Bernard Harrington, and graduated in the newly reorganized Applied Sciences program. He spent the summer of 1874 working as Robert Bell’s assistant in Manitoba, and the following summer working in the Michigan copper mines as an assistant to a mine engineer, Luther Emerson. He obtained a position as science teacher at Hamilton Collegiate Institute (Fig. 1) in 1876. In 1877 he submitted his thesis on Michigan copper deposits to the university at Göttingen, Germany and that summer he visited the university, passed his oral examinations and was awarded the Ph.D., becoming the second Canadian to earn a doctorate in geology. In 1880 he became Professor at King’s College, Windsor, Nova Scotia. He concentrated his geological studies on the region around his birthplace at the head of Lake Ontario: at first mainly Paleozoic geology and paleontology, but by 1880 he had switched decisively to surficial geology, particularly the preglacial drainage of Lakes Erie and Ontario. In 1880 he travelled extensively in the United States and attended the AAAS meeting in Boston, where he met J.P. Lesley, who encouraged him to continue his studies of preglacial rivers. In 1882 he accepted a position as Professor and Director of the Museum of Natural History at the University of Missouri. RÉSUMÉ J.W. Spencer qui est né et a été inhumé chez lui à Dundas en Ontario a été un géomorphologue canadien qui a fait oeuvre de pionnier. Après avoir été à l’école à Dundas, il a déménagé à Hamilton où il a travaillé dans une pharmacie, et c’est à ce moment que des géologues amateurs l’ont encouragé à aller de l’avant. Il a fréquenté l’Université McGill de 1871 à 1874, où il a reçu les enseignements de William Dawson et de Bernard Harrington, et suivi avec succès la formation du programme nouvellement refondu en sciences appliquées. Durant l’été de 1874, il a été l’assistant de Robert Bell au Manitoba et, l’été suivant, il a travaillé dans les mines de cuivre du Michigan où il a été l’assistant Luther Emerson, ingénieur minier. En 1876, il a obtenu le poste de professeur de science à l’Institut collégial Hamilton (Fig. 1). En 1877, il a soumis sa thèse sur les gisements de cuivre du Michigan à l’université de Göttingen en Allemagne, et durant l’été il s’est rendu à l’université, y a passé ses examensoraux, puis a obtenu son Ph.D., devenant le deuxième Canadien a obtenir un doctorat en géologie. En 1880, il est devenu professeur au King’s College, à Windsor en Nouvelle-Écosse. Il a concentré ses recherches géologiques sur la région de son lieu de naissance, à la source du lac Ontario : il s’est d’abord principalement intéressé à la géologie et à la paléontologie du Paléozoïque, mais en 1880 ses intérêts avaient carrément changé pour se porter sur la géologie de la surface, particulièrement le drainage préglaciaire des lacs Ontario et Érié. En 1880, il a beaucoup voyagé aux États-Unis, participant au congrès de l’AAAS (association étasunienne pour l’avancement des sciences) à Boston, où il a rencontré J. P. Lesley qui l’a encouragé à continuer ses recherches sur les cours d’eau pré-glaciaires. En 1882, il a accepté un poste de professeur et de directeur au musée d’histoire naturelle de l’Université du Missouri.